Three-dimensional volume fluorescence-imaging of vascular plasticity in adipose tissues - Ying Cao; Huanhuan Wang; Qi Wang; Xiangli Han; Wenwen Zeng (Elsevier, 2018)
Objective: The vascular system is central to sustaining tissue survival and homeostasis. Blood vessels are densely present in adipose tissues and exert essential roles in their metabolism. However, conventional immunohistochemistry methods have intrinsic limitations in examining the 3D vascular network in adipose tissues as well as other organs in general. Methods: We established a 3D volume fluorescence-imaging technique to visualize the vasculatures in mouse adipose tissues by combining the optimized steps of whole-mount immunolabeling, tissue optical clearing, and lightsheet volume fluorescence-imaging. To demonstrate the strength of this novel imaging procedure, we comprehensively assessed the intra-adipose vasculatures under obese conditions or in response to a cold challenge. Results: We show the entirety of the vascular network in mouse adipose tissues on the whole-tissue level at a single-capillary resolution for the first time in the field. We accurately quantify the pathological changes of vasculatures in adipose tissues in wild-type or obese mice (ob/ob, db/db, or diet-induced obesity). In addition, we identify significant and reversible changes of the intra-adipose vasculatures in the mice subjected to cold challenge (i.e., 4°). Furthermore, we demonstrate that the cold-induced vascular plasticity depends on the sympathetic-derived catecholamine signal and is involved in the beiging process of white adipose tissues. Conclusions: We report a 3D volume fluorescence-imaging procedure that is compatible with many areas of vascular research and is poised to serve the field in future investigations of the vascular system in adipose tissues or other research scenarios. Keywords: 3D volume fluorescence-imaging, Vascular plasticity, Adipose tissues, Sympathetic arborizations, Obesity, Cold-induced beiging